Dominansi dan Seleksi Jamur Aspergillus Perusak Gaplek - Oramahi, H. A.; Sumardiyono, Christanti; Pusposendjojo, Nursamsi; Haryadi, Haryadi (Universitas Atma Jaya Yogyakarta, 2010)
Dried cassava is a suitable host for the growth and development of the genus Aspergillus. Fungi reported to grow on dried cassava were A. clavatus, A. flavus, A. foetidus, A. fumigatus, A. niger, A. ochraceus, A. oryzae, A. tamarii, A. zonatus, dan Aspergillus sp. From those species, A. flavus is the most important species because of its toxigenic characteristic on agricultural product. This study was conducted to study dominant species of Aspergillus causing the most severe deterioration on stored dried cassava and causing the highest deterioration in dried cassava. The isolates were then cultured for determination of dominant species. The in vitro experiment was to obtain the species of Aspergillus that is resulted in highest change of dried cassava spoilage. Based on relative index frequency (Rif) and presence index of the fungus (Pif), A. flavus was the most dominant species and causing the highest deterioration on the dried cassava.